Urban water supply management through multi-objective optimization - Ong, Anurad Ching Chin. (2012)
While previously the water supply management focuses on optimizing a single objective such as minimizing the leakage in the water supply chain or maximizing gross margins, today’s socio-economic pressure forces decision makers to look into other objectives and manage urban water supply as an integrated whole. These objectives include fulfilling the demand of the consumers while delivering the desired level of water quality, and minimizing the operation and transportation costs. Thus, this paper aims to study how multi-objective optimization can contribute in the area of urban water supply. Three different multi-objective optimization forms have been selected and applied to a water supply model and the underlying fundamental philosophy behind the different methods is studied. In this paper, the Hamedan potable water network is selected for the case study. Results show that multi-objective optimization is able to produce better results than single-objective optimization. However, the selection of a suitable multi-optimization model is a challenging task as it is highly dependent on the preferences of the decision maker.